Distribution characteristics of organochlorine pesticides in soil, water, and sediment from the Bahe River, China. Issue 1 (2nd January 2016) - Lu, Hongxuan; Liu, Weiguo
ABSTRACT: The concentrations and distributions of organochlorine pesticides in multiple matrices (soil, water, sediment) along the Bahe River were determined. Overall, the levels of total hexachlorocyclohexanes (HCHs) in water, sediments, and soils detected by GC-μECD ranged from n.d. to 0.74 ng/L, n.d. to 1.02 ng/g, and 0.02 to 0.32 ng/g, respectively. The levels of total dichlorodiphenyltrichloroethanes (DDTs) in water, sediments, and soils ranged from n.d. to 7.51 ng/L, n.d. to 0.29 ng/g, and 0.03 to 2.00 ng/g, respectively. The relationships between the parent compounds and their metabolite were used to assess the source of the organochlorine pesticides (OCPs). The low α-HCH/γ-HCH ratios indicated that technical HCHs were mainly from historical usage or implied the presence of a possible emission source of lindane, while the relatively high ratio of p, p′-DDT/p, p′-dichlorodiphenyldichloroethylene (DDEs) suggested the possibility of a recent fresh input of DDTs in this area. All the soil and water were classified as exhibiting low levels of OCP pollution according to the Chinese guidelines for the environmental quality standard for soils (GB 15618–1995) and surface water (GB 3838–2002). The concentrations in all sediment samples were far below the threshold effect level set up by the Canadian Council of Ministers of the Environment (2002 ).